Healing, grief, and the philosophy of thought in the works of Frances Burnett - Adilova, Fotimaxon Muxammad Anasovna (The Lingua Spectrum, 2026)
This article examines the psychological and philosophical dimensions of Frances Hodgson Burnett’s major works, arguing that her fiction constitutes a coherent therapeutic vision that extends well beyond the conventions of Victorian and Edwardian children’s literature. Drawing on The Secret Garden (1911) and A Little Princess (1905), the analysis identifies five interconnected thematic strands: the garden as a metaphor for psychic restoration and active self-recovery; the influence of the New Thought movement on Burnett’s treatment of belief, volition, and physical health; the complex and unsentimental portrayal of grief in the figure of Archibald Craven; the Stoic philosophy of interior sovereignty enacted by Sara Crewe; and the proto-ecopsychological conviction that sustained contact with the natural world carries measurable restorative properties. The article contends that Burnett arrived, through narrative instinct and personal experience of loss, at insights that anticipate modern developments in cognitive behavioral therapy, relational systems theory, and nature-based medicine. Rather than positioning her works as naive celebrations of positive thinking, the analysis attends to their philosophical complexity, including their honest reckoning with the limits of will, the costs of imagination, and the irrational dimensions of human recovery.